Pelaksanaan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Di SD Negeri Se-Kecamatan Tanjung Kemuning Kabupaten Kaur: Implementation of Physical Education Learning in Sports and Health in State Elementary Schools throughout the Tanjung Kemuning District, Kaur Regency - Anton Trimarno; Dian Pujianto; Arwin (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Abstract This study aims to determine the implementation of PJOK learning in State Elementary Schools throughout the Tanjung Kemuning Kaur District. This research is a type of field research using descriptive qualitative methods. The informants in this study were 11 PJOK teachers and several representatives of class V students as many as 3 people from each State Elementary School in Tanjung Kemuning District. Data collection techniques with observation, questionnaires and documentation. The results showed that the overall ability of physical education teachers in public elementary schools throughout the Tanjung Kemuning district was included in the good criteria with a percentage of 69.82%. Overall, the condition of students in physical education learning at public elementary schools throughout the Tanjung Kemuning sub-district has entered the good criteria with a percentage of 69.44%. However, there are some schools with very good and good scores. The highest score was obtained by SD Negeri 44 with a score of 35 and the lowest score was obtained by SD Negeri 37 with a score of 22. Keywords: Implementation, Learning, Physical Education, Sports and Healt